Accuracy and Precision of Computer-assisted Navigation Compared With Patient-Specific Instrumentation and Conventional Methods in Total Ankle Arthroplasty - Cole Herbel; Ramiro Lopez; Matt Rueff; Zachary Tupper; Cyril Hamad; Edward T. Haupt (Journal of the American Academy of Orthopaedic Surgeons, 2026)
Introduction: Total ankle arthroplasty (TAA) has become a viable alternative to ankle arthrodesis (AA) in recent years. However, implant longevity is a concern because malalignment of either the tibial or talar implants has been shown to predispose to premature wear and necessary revision surgery. Thus, customized surgical tools such as computer navigation and patient-specific instrumentation have been used to theoretically improve intraoperative alignment of implants. The primary outcome of this study is to compare alignment between a computer-assisted navigation (CAN) system for TAA, a preexisting patient-specific instrumentation (PSI) system, and SRG fluoroscopic techniques. Methods: TAA was done on 36 artificial ankle joint specimens by a single surgeon: 12 using CAN, 12 with PSI, and 12 with SRG instrumentation. All specimens were scanned both preoperatively and postoperatively using a high-precision 3D scanning tool. Resections and implant placements were then analyzed in 3D processing software and compared between surgical modalities. Statistical analysis included one-way ANOVA with associated Tukey tests to assess for differences between groups. Results: We found that tibial resections were overall most accurate using CAN, with tibial slope measurements demonstrating significant improvements over PSI ( P < 0.001) and conventional instrumentation ( P < 0.001). PSI was more accurate than SRG when considering the axial cut height of the tibial resection ( P < 0.001). In the talar resections, CAN was statistically superior to SRG methods in two of three measured categories (slope: P < 0.001, axial cut height: P < 0.001). However, PSI fared better than CAN in those same categories (slope: P = 0.002, axial cut height: P < 0.001). Employment of the CAN system also decreased implant placement variability (CAN: ± 0.47 mm, ± 0.62 deg; PSI: ± 0.63 mm, ± 1.03 deg; SRG: ± 0.73 mm, ± 1.21 deg). Conclusion: In this laboratory-based TAA study, we found that both CAN and PSI demonstrated advantages over SRG instrumentation regarding implant placement accuracy. Tibial resections were found to be overall most accurate under CAN guidance, and talar resections were found to be overall most accurate under PSI guidance. In addition, the observed reduction in implant placement variability has potential positive implications for surgeons. However, as this study was conducted on artificial specimens, effects of soft tissue and preoperative deformities or pathologies were not considered. Future studies should include cadaveric specimens with various pathologies to better simulate conditions encountered in an operating room. Level of Evidence: Level II – Lesser Quality RCT or Prospective Comparative Study.